Kebijakan Dividen dalam Situasi Ketidakpastian Politik - Bhenu Artha (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
Political uncertainty has an impact on the company's dividend payment policy. Political uncertainty proxied by national elections is a significant contributor to information asymmetry in financial markets. Companies will try to maintain dividend payments to shareholders to show that the company is not affected by political uncertainty characterized by the implementation of general elections. This study aims to determine the effect of political uncertainty on dividend policy. The novelty in this study is the existence of general elections that simultaneously elect five institutions, namely the DPR, DPD, DPRD I, DPRD II and the President and Vice President. The sample of this research is 322 companies listed on the Indonesia Stock Exchange. The results showed that political uncertainty has no effect on dividend policy. The company will always try to maintain the welfare of shareholders through dividend policy, regardless of conditions.